Smear layer-deproteinizing improves bonding of one-step self-etch adhesives to dentin - Ornnicha Thanatvarakorn (2018)
© 2018 The Academy of Dental Materials Objectives: Smear layer deproteinizing was proved to reduce the organic phase of smear layer covered on dentin surface. It was shown to eliminate hybridized smear layer and nanoleakage expression in resin–dentin bonding interface of two-step self-etch adhesive. This study aimed to investigate those effects on various one-step self-etch adhesives. Methods: Four different one-step self-etch adhesives were used in this study; SE One (SE), Scotchbond™ Universal (SU), BeautiBond Multi (BB), and Bond Force (BF). Flat human dentin surfaces with standardized smear layer were prepared. Smear layer deproteinizing was carried out by the application of 50 ppm hypochlorous acid (HOCl) on dentin surface for 15 s followed by Accel®(p-toluenesulfinic acid salt) for 5 s prior to adhesive application. No surface pretreatment was used as control. Microtensile bond strength (μTBS) and nanoleakage under TEM observation were investigated. The data were analyzed by two-way ANOVA and Tukey's post-hoc test and t-test at the significant level of 0.05. Results: Smear layer deproteinizing significantly improved μTBS of SE, SU, and BB (p < 0.001). Hybridized smear layer observed in control groups of SE, BB, and BF, and reticular nanoleakage presented throughout the hybridized complex in control groups of BB and BF were eliminated upon the smear layer deproteinizing. Significance: Smear layer deproteinizing by HOCl and Accel®application could enhance the quality of dentin for bonding to one-step self-etch adhesives, resulting in the improving μTBS, eliminating hybridized smear layer and preventing reticular nanoleakage formation in resin–dentin bonding interface.